[21+(-9)+(-12)+(-43)]+[-(-67)]

[21+(-9)+(-12)+(-43)]+[-(-67)]

2 bình luận về “[21+(-9)+(-12)+(-43)]+[-(-67)]”

  1. Giải đáp:+Lời giải và giải thích chi tiết:
     [21+(-9)+(-12)+(-43)]+[-(-67)]
    =[21+(-9)+(-12)+(-43)]+67
    = [(-9) + (-12)] + 21 + (-43) + 67
    = (-21) + 21 + (-43) + 67
    = 0 + (-43) + 67
    = -43 + 67
    = 24

    Trả lời
  2. Giải đáp:
    24
    Lời giải và giải thích chi tiết:
    [21 + (-9) + (-12) + (-43)] + [-(-67)]
    =21 + (-9) + (-12) + (-43)  + 67
    =12+(-12) + (-43) + 67
    =0 + (-43) + 67
    =67 + (-43)
    =24

    Trả lời

Viết một bình luận

Câu hỏi mới